A provocative call to engage with social and sensory aspects of touch. Issue 3 (September 2022) - Jewitt, Carey; Price, Sara; Steimle, Jürgen; Huisman, Gijs; Golmohammadi, Lili; Pourjafarian, Narges; Frier, William; Howard, Thomas; Ipakchian Askari, Sima; Ornati, Michela; Paneels, Sabrina; Weda, Judith
The social and sensory aspects of touch are critical for human communication, yet the challenges of haptic technology development and a focus on the technological means that digital touch communication often fails to realise the potential and promise of touch. The Manifesto for Digital Social Touch in Crisis responds to this through a call to action to rethink and reimagine digital touch. It offers 10 provocative statements as a resource for how haptic designers, developers and researchers might rethink and reimagine the social and sensory aspects of touch, and foreground these more in design.